ТАХТАКӨПИР РАЙОНЫ ТОПОНИМЛЕРИНИҢ ПАЙДА БОЛЫЎ СЕБЕПЛЕРИ ҲАҚҚЫНДА - Серикбаева, А.С. (ILIM hám JÁMIYET, 2021)
Each toponym, hydronym, oronym has a secret and history of naming. The article discusses the origin of naming some toponyms of Takhtakopir region,which full of rich toponymic information.